Peran Moral Disengagement dalam Meningkatkan Pengaruh Cognitive Distortion dan Displaced Aggression pada Dewasa Awal Korban Cyberbullying - Rukmana, Andi Novianti; Soetikno, Naomi; Satyadi, Heryanti (Universitas Muhammadiyah Metro, 2025)
Indonesia occupies the fourth position with the most internet users in the world (Prasasti, 2022), the MENKOMINFO further stated that internet users in Indonesia account for 73.7 percent of the total population. The increase in internet users in Indonesia is in line with the raising cases of cyberbullying, UNICEF (2022) states that 12 percent of victims of cyberbullying become perpetrators of cyberbullying. The aim of this research is to see the effect of cognitive distortion on displaced aggression and the moderating effect of moral disengagement. The research method used was quantitative with purposive sampling data collection techniques, and the data were analyzed using moderated regression analysis with the help of SPSS version 21. The study participants totaled 135 people, most of the participants were women (n = 78), and the average participant was at very high cognitive distortion (n=64), moderate moral disengagement (n=63), and very high displaced aggression (n=65). The results of the analysis show that cognitive distortion causes a person to experience displaced aggression (β=0.466; p0.05), but several dimensions of moral disengagement have a significant influence including moral justification (β=0.280; p<0.01). In conclusion, this study found that cognitive distortion affects displaced aggression behavior in victims of cyberbullying and moral disengagement in this research has an influence on displaced aggression as an independent variable but does not moderate the relationship between cognitive distortion and displaced aggression (predictor of moderation).